ApoE ɛ4 genotype and the age at onset of temporal lobe epilepsy: A case-control study and meta-analysis. - Kauffman, Marcelo Andres (2010)
In order to investigate the role of ApoE e{open}4 as a modifier of the age at onset of temporal lobe epilepsy (TLE), we performed a molecular epidemiology study in 78 patients with mesial temporal lobe epilepsy and hippocampal sclerosis. Genotyping was done by a PCR-RFLP assay. In order to better estimate the role of this variant as a modifier of the age at onset, we also performed a systematic review of the literature. We included our results into a meta-analysis along with data available from seven published studies with 728 patients that looked into the role of ApoE e{open}4 in TLE. We found that ApoE e{open}4 carriers in our population had a non-significant earlier age of epilepsy onset than non-carriers. The meta-analysis confirmed this finding, showing that ApoE e{open}4 carriers had epilepsy onset almost 4 years earlier than non-carriers (mean difference 5.15 years; CI 95% 2.08-6.22; p=0.001). In conclusion, the ApoE e{open}4 isoform is a genetic factor that might influence the age at onset of TLE.